Relationships between volume and pressure measurements and stroke volume in critically ill patients - Bindels, Alexander JGH (BioMed Central, 2000)
OBJECTIVE: To evaluate the relationships between the changes in stroke volume index (SVI), measured in both the aorta and the pulmonary artery, and the changes in intrathoracic blood volume index (ITBVI), as well as the relationship between changes in aortic SVI and changes in the pulmonary artery wedge pressure (PAWP). DESIGN: Prospective study with measurements at predetermined intervals. SETTING: Medical intensive care unit of a university hospital. PATIENTS AND METHODS: One hundred and fifty-four measurements were taken in 45 critically ill patients with varying underlying disorders. Aortic SVI and pulmonary arterial SVI were determined with thermodilution. PAWP was measured using a pulmonary artery catheter. ITBVI was determined with thermal-dye dilution, using a commercially available computer system. RESULTS: A good correlation was found between changes in ITBVI and changes in aortic SVI. However, this correlation weakened when changes in ITBVI were plotted against changes in pulmonary arterial SVI, which was in part probably due to mathematical coupling between ITBVI and aortic SVI. A good correlation between changes in ITBVI and changes in aortic SVI could also be established in most of the individual patients. No correlation was found between changes in PAWP and changes in aortic SVI. CONCLUSION: ITBVI seems to be a better predictor of SVI than PAWP. ITBVI may be more suitable than PAWP for assessing cardiac filling in clinical practice.